O idoso e a cidade: a qualidade do espaço urbano do Centro de Fortaleza - Lima, Manuela de Castro Mendonça (2021)
Considering that the elderly population in Brazil is gradually increasing and the right to come and go, present in the Brazilian Constitution of 1988, should instigate public policies that will favor this portion of the population, the need for accessibility in the cities constructed environment present itself as a prominent parameter to contribute to the viability of new actions in the field of Architecture, Urbanism and Design. In this context, the present research analyzes, within the scope of urban spatial quality, with a focus on accessibility, the Center of the city of Fortaleza, aiming to perceive how the current reality of the place interferes in the daily, physical security and emotional state of the elderly person. As a methodology, the documentary and bibliographic research procedures about aging and urban issues involving the elderly were initially used, where a literature review can be carried out about this subject during the last decade, in addition to contextualizing the biopsychosocial issues of aging. It was also observed concepts of sustainable cities and their relationship with the elderly. As procedures for the field research procedures, on-the-spot surveys and exploratory tours were carried out, what made it possible to understand the current physical situation of the place. Thus, the spatial area of the present research aims to analyze, in a qualitative way, a section of the Center of Fortaleza and the relationship with the quality and fluidity of the use of space by the elderly, in order to present the points that stand out the most as problems for this public and collaborate for possible new actions and public policy guidelines.